2011
DOI: 10.5539/ass.v7n12p216
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Halal Food amongst Food Industry Entrepreneurs in Malaysia

Abstract: Food industry becomes one of the main sources of income for local community in Malaysia. Thus knowledge on halal food is so crucial to be studied. This paper tends to investigate some types of traditional halal food and to analyse the entrepreneurs’ knowledge on the subject. To meet these objectives, a set of questionnaire was then constructed to gather information on the issue. Using the non-probability sampling techniques, about 300 food industry entrepreneurs from the State of Terengganu and Kelantan were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…Existing study about knowledge has discussed on knowledge about Halal food among food manufacturers in Malaysia aimed at measuring the knowledge level on food hygiene and the concept of halal food amongst the food industries entrepreneurs [11]. The results found that majority of the marketers have a sufficient knowledge about Halal food and they are aware that food which contained with unslaughtered or diseased animals is forbidden according to Muslim rites.…”
Section: Literature Review and Hypothesis Formationmentioning
confidence: 74%
“…Existing study about knowledge has discussed on knowledge about Halal food among food manufacturers in Malaysia aimed at measuring the knowledge level on food hygiene and the concept of halal food amongst the food industries entrepreneurs [11]. The results found that majority of the marketers have a sufficient knowledge about Halal food and they are aware that food which contained with unslaughtered or diseased animals is forbidden according to Muslim rites.…”
Section: Literature Review and Hypothesis Formationmentioning
confidence: 74%
“…Consumers have sound knowledge on the concept of Halal, but they still have low awareness regarding Halal certification and Halal label 14 . However, knowledge was influenced by the level of understanding gained from information that revealed more details about Halal products 15 . Knowledge contributes to consumers' buying behavior, product information searches, and product evaluations [16][17][18] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the highest market in this country, Muslim consumers are undoubtedly ascertained that the food products obtained or, buying from any market place should religiously fit for their consumption (Rahman, Ahmad, Mohamad, & Ismail, 2011;Ambali & Bakar, 2014). The concern relates to the halalness of the ingredients used, preparation and cleanliness of the products either on dry, wet, fresh, canned or processed (Dindyal, 2003).…”
Section: Syubhah Food and Consumermentioning
confidence: 99%